Ask the audience: evaluating new ways to fund TV content - Kevill, S; Connock, A (Reuters Institute for the Study of Journalism, 2013)
This report examines the evolving funding and distribution models for TV and video content and the global debate around editorial credibility, regulation, and effectiveness. It asks viewers what they think of content created in this way and demonstrates a surprisingly high tolerance of advertiser presence.